2021
DOI: 10.1038/s41467-021-22596-0
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of AMPylation of the human chaperone BiP is mediated by TPR motifs of FICD

Abstract: To adapt to fluctuating protein folding loads in the endoplasmic reticulum (ER), the Hsp70 chaperone BiP is reversibly modified with adenosine monophosphate (AMP) by the ER-resident Fic-enzyme FICD/HYPE. The structural basis for BiP binding and AMPylation by FICD has remained elusive due to the transient nature of the enzyme-substrate-complex. Here, we use thiol-reactive derivatives of the cosubstrate adenosine triphosphate (ATP) to covalently stabilize the transient FICD:BiP complex and determine its crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 77 publications
4
21
0
12
Order By: Relevance
“…Enzymes that mediate protein NMPylation frequently have low affinity for their targets, necessitating covalent linkage of enzyme:substrate complexes for structural analysis ( 41 ). The modified nsp9 appears to be released from SARS-CoV-2 RdRp ( Supplementary Figure S3A ) and multi-round NMPylation of HCoV-229E nsp9 has also been reported ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes that mediate protein NMPylation frequently have low affinity for their targets, necessitating covalent linkage of enzyme:substrate complexes for structural analysis ( 41 ). The modified nsp9 appears to be released from SARS-CoV-2 RdRp ( Supplementary Figure S3A ) and multi-round NMPylation of HCoV-229E nsp9 has also been reported ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst this manuscript was in revision we became aware of a crystal structure of BiP covalently bound to FICD (PDB 6ZMD ) 34 , likely that of a transient intermediate post-AMPylation state. This covalent complex possess a near-identical FICD(TPR)–BiP interface to the deAMPylation complexes presented here, which accounts for the consistent outcome of the mutagenesis carried out in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…( A ) FICD is comprised of a short N-terminal cytosolic tail, a transmembrane domain (TM; dark grey), two tetratricopeptide repeats (TPR; turquoise), a linker (yellow), and the catalytic Fic domain (FIC; blue). The segment for which crystal structures have been solved (approximately residues 102 to 445 depending on the particular study) is indicated [ 10 , 11 , 12 , 22 ]. The numbers denote residue positions that mark the boundaries of key regions in the structure of FICD.…”
Section: Figurementioning
confidence: 99%
“…Moreover, while single-pass membrane proteins such as FICD represent roughly half of all membrane proteins, structural studies of these are limited [ 24 , 29 , 30 ]. The currently available crystal structures of FICD include the catalytic domain and the adjacent tetratricopeptide repeats (TPRs) ( Figure 1 B) [ 10 , 11 , 12 , 22 ]. In vitro investigations of FICD’s structure and enzymatic mechanism have been conducted using N-terminally truncated (lacking the first approximately 100 residues), soluble protein variants produced in E. coli .…”
Section: Introductionmentioning
confidence: 99%